NANOPARTIKEL PERAK - Khairiza Lubis (Universitas Negeri Medan, 2015)
Silver nanoparticles have many benefits in human life. Many products that are used in daily life that use ingredients derived from silver nanoparticles. Among such as soap, toothpaste, towels and so forth. This is because the silver nanoparticles have unique properties. In addition to having positive benefits for human life, silver nanoparticles also have a negative impact on human life and other organisms as well, such as silver nanoparticles have a high toxicity against larvae and adult mosquitoes. In synthesizing silver nanoparticles can be carried out chemical and biological. This article discusses: the nature, benefits, synthesis, and effect of silver nanoparticles. Keywords: nanoparticle, silver